2010
DOI: 10.1111/j.1420-9101.2010.02199.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of sex on the mean and variance of fitness in facultatively sexual rotifers

Abstract: The evolution of sex is a classic problem in evolutionary biology. While this topic has been the focus of much theoretical work, there is a serious dearth of empirical data. A simple yet fundamental question is how sex affects the mean and variance in fitness. Despite its importance to the theory, this type of data is available for only a handful of taxa. Here, we report two experiments in which we measure the effect of sex on the mean and variance in fitness in the monogonont rotifer, Brachionus calyciflorus.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 61 publications
4
37
0
Order By: Relevance
“…Despite its importance to theory, the effect of sex on the distribution of offspring fitness has been measured in only a handful of taxa [45],[53][57]. In several of those cases [54],[55],[57], sex has been observed to reduce the mean but increase the variance, suggesting that long-term advantages to sex may be reasonably common but in none of those previous cases were evolutionary changes in the rate of sex measured.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite its importance to theory, the effect of sex on the distribution of offspring fitness has been measured in only a handful of taxa [45],[53][57]. In several of those cases [54],[55],[57], sex has been observed to reduce the mean but increase the variance, suggesting that long-term advantages to sex may be reasonably common but in none of those previous cases were evolutionary changes in the rate of sex measured.…”
Section: Discussionmentioning
confidence: 99%
“…The rotifers for this study descended from a population collected from sediment taken from Lake Onondaga, New York, in spring 2009 [45]. The populations used here were started from lab stocks that have previously been adapted to two different food conditions, Environments A and B (which we have previously called “low” and “high” food conditions [17]).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We addressed the question of whether sexual reproduction confers higher variance in fitness‐related traits relative to asexuals by comparing the variance for each of the three life history traits that we measured in sexual and asexual P. antipodarum (following Becks and Agrawal 2011). We began by using a variance components analysis to estimate the variance of each trait for each of the 12 sexual and 93 asexual families that we included in our experiment.…”
Section: Methodsmentioning
confidence: 99%
“…There is currently one study that demonstrated a cost of recombination in rotifers. Becks and Agrawal (66) found that, in benign laboratory environments, sexually produced offspring in Brachionus rotifers were on average less fit than asexually produced offspring. However, this comparison was done within cyclical parthenogenetic clones, so the authors compared the two reproductive modes within the same strains.…”
Section: Empirical Measurements Of Costsmentioning
confidence: 99%